Statistics of Perception Role Ulama on Smoke-Free Policy: Can Implementation of Banda Aceh City? - Muazzinah; Heru Syah Putra; Dian Safitri, Winny; Nadia Ulfah (Universitas Airlangga, 2024)
Background: Smoking control policies' effectiveness requires all parties' active role. In Aceh, as a region that implements Islamic law, religious leaders and ulama are an important part of the success of a policy, including the smoke-free area (SFA) policy. There is no research yet related to the ulama's involvement and role in Banda Aceh's SFA policy. Objective: Therefore, this research aims to examine the citizen's perception of the roles of religious leaders and ulama in supporting SFA policy in Banda Aceh City. A total of 202 respondents were randomly selected to provide their perceptions. Methods: This study utilizes a mixed-methods approach, comprising a survey of perceptions followed by an in-depth literature review. Results: The research findings indicate that out of 202 respondents, 88.00 percent are aware of the Smoke-Free Areas (SFA) policy, with 85.64 percent strongly supporting its implementation. However, concerning the religious leaders' fatwas, only 34.65 percent are well-informed and understand about it. The involvement of religious leaders in policy formulation, dissemination, and monitoring exceeds 50.00 percent, although around 15 percent of respondents perceive a lack of involvement. Conclusion: Regarding the presence of smoke-free mosques and Islamic schools, the majority of the participants perceive it as still limited. 16.34 percent believe there are no smoke-free Islamic boarding schools, and 19.31 percent perceive that mosques in Banda Aceh are not yet smoke-free. The community also hopes that religious scholars will show a direct model by refraining from consuming cigarettes themselves.